The synthesis and reactions of a modified cobalt corrin - Nowakowska, Monika (My University, 2018)
The typically inert Co(III) ion exhibits remarkable lability when encapsulated in a corrin macrocycle such as in vitamin B12. It has been postulated that this lability arises from a significant kinetic cis-effect through the delocalisation of electron density from the relatively electron-rich corrin to Co(III), thus conferring to it a degree of soft, labile Co(II)-like character. We suggest that structural and electronic modifications of the corrin should modulate the transfer of electron density to the central Co(III) ion, thus changing its electronic character. Another important feature of the corrin ring is the relatively small macrocyclic cavity. It appears that Co(III) may be compressed within the corrin macrocycle, which is likely to significantly impact its chemistry. To evaluate what effect these factors may have on the chemistry of Co(III), we prepared a vitamin B12 derivative, Coα,Coβ-dicyano-5,6-dioxo-5,6-seco-heptamethylcob(III)yrinate, [DC-5-seco-Cbs], by perturbing the electronic structure of the dicyanocobyrinic acid heptamethyl ester, Coα,Coβ-dicyano-heptamethylcob(III)yrinate ([DCCbs]) through a photosensitized oxygenation reaction. Not only does this disrupt the partially conjugated system of a normal corrin ring, but the bond between C5 and C6 has been cleaved such that the equatorial ligand of Co(III) is no longer macrocyclic, thereby relieving the steric constraints surrounding the axial coordination site of Co(III) corrins. The secocobester was then converted to the aquacyano derivative, Coα,Coβ-aquacyano-5,6-dioxo-5,6-seco-heptamethylcob(III)yrinate, [AC-5-seco-Cbs]+, in which a coordinated water could be readily displaced by an exogenous ligand in solution chemistry investigations. The effect of these structural modifications was evaluated by comparing analogous thermodynamic and kinetic data for [AC-5-seco-Cbs]+ with aquacyanocobyrinic acid heptamethyl ester (aquacyanocobester, [ACCbs]+), a corrin with an intact delocalised system (the values were re-determined in this study), and aquacyano-stable yellow-cobester, ([ACSYCbs]+), a corrin with a diminished delocalised π electron system, to observe the effect the nature of the corrin ring has on the properties of the Co(III) ion. The pKa for ionization of coordinated water decreases from 9.8 ± 0.3 in [ACCbs]+ to 7.28 at 25 oC (ΔH = –88 ± 17 kJ mol–1 and ΔS = –434 ± 56 J K–1 mol–1) in [AC-5-seco-Cbs]+. The unusually low pKa, confirmed by determining the pH-dependence of the coordination of SO32– by [AC-5-seco-Cbs]+, shows Co(III) in this complex behaves much more like Co(III) in simple hexacoordinate complexes than in intact cobalt corrins. A comparison of log K values the for coordination of CN–, SO22–, NO2–, N3– and S2O32– demonstrates that cleavage of the corrin ring significantly decreases the affinity of Co(III) for the softer ligands CN–, SO32– and, more marginally, NO2–. However, [AC-5-seco-Cbs]+ has a higher affinity for N3– and S2O32– than [ACCbs]+. These trends correlate with the position of the ligands in the spectrochemical series (N3– < S2O32– < NO2– < SO32– < CN–); the first two behave as π donors towards metal ions, and the last three as π acceptors. Cleavage of the corrin, with a concomitant increase in hardness of the metal, decreases it affinity for π acceptors while the thermodynamic stability of its complexes with π donors increases as the metal ion becomes more Co(III)-like, and more capable of accepting electron density from the ligand. The temperature-dependence of log K values show very negative values for ΔH offset by ΔS values which are also large and negative. In the absence of crystal structures, DFT methods (BP86-D3/6-311G(d,p)) were used to assess the structural consequences of cleavage of the corrin. The topological properties of the electron density were assessed using Bader’s Quantum Theory of Atoms in Molecules (QTAIM). The cleavage of the corrin does not unduly perturb the coordination sphere of the metal ion and the metal remains essentially octahedral. The sum of the partial charges on the metal and the entire coordination sphere, or the metal and the four equatorial donor N atoms, is less negative in the 5-seco-Cbs complexes than in the Cbs themselves and supports the supposition that cleavage of the corrin has made the metal and its immediate environment more positive. A brief look into the binding of neutral N-donor ligands (N-MeIm, 4-MePy and NH2EtOH) showed that the distinction between the softer Co(III) in [ACCbs]+ and the harder Co(III) in [AC-5-seco-Cbs]+ ([ACCbs]+ > [ACSYCbs]+ > [AC-5-seco-Cbs]+) observed for the binding of anionic ligands was maintained for the neutral N-donor ligands. Furthermore, results also indicated that relieving the steric hindrance surrounding the axial coordination site in [AC-5-seco-Cbs]+ did enhance the metal’s ability to bind larger neutral ligands. To probe the cis-labilising effect of the corrins, kinetics data for the substitution of water trans to a cyanide moiety with a probe ligand, cyanide, were obtained under pseudo first-order conditions. The substitution of water coordinated to Co(III) by cyanide showed biphasic kinetics. The faster reaction was attributed to substitution of H2O by CN– trans to CN–, and the slower phase to the reaction of the diaqua complex with CN–, i.e., substitution of H2O trans to H2O. The rate of substitution of H2O by CN– in [AC-5-seco-Cbs]+ is some two orders of magnitude slower than the substitution of H2O by CN– in [ACCbs]+. Cleavage of the corrin together with the release of Co(III) from the small cavity of the corrin has therefore significantly decreased the lability of Co(III). For interest, the data were compared to analogous data for aquacobalamin. In this way, the effect of the ligand trans to the axially coordinated water on its substitution could be elucidated. It was found that as the trans ligand varied from cyanide to dimethylbenzimidazole (DMBz) ([AC-5-seco-Cbs]+ to aquacobalamin), the rate constant increased from kII ≈ 102 M–1s–1 to 7.87 × 102 M–1s–1; hence cracking of the corrin ring and the associated opening of the macrocyclic cavity results in an even more pronounced inert Co(III) character. This study demonstrates how perturbation of the electronic structure of the corrin in cobalt corrin complexes significantly affects the coordination chemistry of the axial coordination sites and points to the importance of cis effects in cobalt corrin chemistry.
A thesis submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the Degree of Doctor of Philosophy. June 2018